Strategic Planning in Educational Organization at Dahniar Public Elementary School, Bandung Regency (Qualitative Descriptive Study at Dahniar Public Elementary School, Bandung Regency) - Dhita Annisa Fauzia; Dina Hairun Nissa; Hilman Farouq Ghoer; Helmawati Helmawati (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Strategic planning in educational organizations is a process that helps institutions determine long-term goals, analyze internal and external factors, and develop steps to achieve these goals. This planning is important to ensure the adaptability and effectiveness of educational institutions in the face of environmental changes, especially in the digital era. This article discusses the definition, process, benefits and challenges of strategic planning in educational organizations. With a comprehensive approach, strategic planning helps educational organizations to adapt to technological innovations and the changing needs of society. Strategic planning is an important component in effective school management, which aims to achieve the vision and mission that have been set. This scientific work examines innovations in strategic planning as an effort to align the school's vision and mission with the needs of the school organization. This research uses a qualitative method with a case study approach in several schools that have implemented innovation-based strategic planning. The results show that innovations in strategic planning, such as the application of information technology and the participatory involvement of all school elements, can strengthen the alignment between the vision, mission and organizational needs. Thus, these innovations can improve operational efficiency and build an organizational culture that is adaptive to change. In conclusion, innovation in strategic planning not only clarifies the direction and goals of the school, but also supports the creation of a more dynamic learning environment that is responsive to future challenges.